Deregulation of microtubule organization and RNA metabolism in Arx models for lissencephaly and developmental epileptic encephalopathy. Issue 11 (31st January 2022) - Drongitis, Denise; Caterino, Marianna; Verrillo, Lucia; Santonicola, Pamela; Costanzo, Michele; Poeta, Loredana; Attianese, Benedetta; Barra, Adriano; Terrone, Gaetano; Lioi, Maria Brigida; Paladino, Simona; Di Schiavi, Elia; et al.
Abstract: X-linked lissencephaly with abnormal genitalia (XLAG) and developmental epileptic encephalopathy-1 (DEE1) are caused by mutations in the Aristaless-related homeobox ( ARX ) gene, which encodes a transcription factor responsible for brain development. It has been unknown whether the phenotypically diverse XLAG and DEE1 phenotypes may converge on shared pathways. To address this question, a label-free quantitative proteomic approach was applied to the neonatal brain of Arx knockout ( Arx KO/Y ) and knock-in polyalanine ( Arx (GCG)7/Y ) mice that are respectively models for XLAG and DEE1. Gene ontology and protein–protein interaction analysis revealed that cytoskeleton, protein synthesis and splicing control are deregulated in an allelic-dependent manner. Decreased α-tubulin content was observed both in Arx mice and Arx/alr-1 ( KO ) Caenorhabditis elegans, and a disorganized neurite network in murine primary neurons was consistent with an allelic-dependent secondary tubulinopathy. As distinct features of Arx (GCG)7/Y mice, we detected eIF4A2 overexpression and translational suppression in cortex and primary neurons. Allelic-dependent differences were also established in alternative splicing (AS) regulated by PUF60 and SAM68. Abnormal AS repertoires in Neurexin-1, a gene encoding multiple pre-synaptic organizers implicated in synaptic remodelling, were detected in Arx/alr-1 ( KO ) animals and in Arx (GCG)7/Y epileptogenic brain areas and depolarized cortical neurons. Consistent with a conserved role of ARX in modulating AS, we propose that the allelic-dependent secondary synaptopathy results from an aberrant Neurexin-1 repertoire. Overall, our data reveal alterations mirroring the overlapping and variant effects caused by null and polyalanine expanded mutations in ARX . The identification of these effects can aid in the design of pathway-guided therapy for ARX endophenotypes and NDDs with overlapping comorbidities. Graphical abstract: